'We're not the hottest ethnicity': Pacific scholars and the cultural politics of New Zealand universities. (8th August 2019) - Kidman, Joanna; Chu, Cherie
ABSTRACT: Academic labour markets around the world are increasingly globalised and tied to transnational circuits of neoliberal capital. Universities in New Zealand are closely aligned with these trends and an academic labour force has developed over time that reflects these economic flows and currents. This labour force is characterised by an exceptionally high number of multinational academic staff, many of whom contribute to research and inquiry aimed at maintaining and broadening the influence of their institutions abroad. Pacific faculty, however, experience the micro-geographies of New Zealand universities in different ways from other migrant scholars, especially those who hail from the global North. They are rarely included in academic 'prestige economies' or elite scholarly networks and are often isolated in their academic departments. This paper draws on a study about the experiences of senior Pacific academics in Aotearoa New Zealand and explores how they formulate pan-Pacific solidarities within the neoliberal and settler-colonial milieu of higher education. We focus on the often fraught dynamics of encounters between Pacific scholars, white academic elites and indigenous Māori colleagues as they map academic identities on to institutional space.